Implementation of Mortgage Guarantee in Housing Financing through Musyārakah Mutanāqiṣah Contract - Amir, A. M. Nur Atma; Parmitasari, Rika Dwi Ayu; Muin, Rahmawati; Awaluddin, Murtiadi; Arsyad, Kamaruddin; Wahyudi, Iqmal (Al-Jadwa: Jurnal Studi Islam, 2025)
In the banking system, collateral serves as a crucial tool for protecting creditors and ensuring debtors fulfill their obligations, particularly in transactions involving valuable assets like property. This study aims to analyze the implementation of collateral in the Musyārakah Mutanāqiṣah Contract on the Hijrah Home Ownership product at Bank Muamalat Indonesia (BMI) Makassar Branch and to evaluate the suitability of the application of collateral in housing financing through the Musyārakah Mutanāqiṣah Contract with Islamic economic principles. This study is included in the category of field research by implementing descriptive qualitative research procedures and using phenomenological and juridical-normative approaches. This study was conducted using four data collection techniques, namely participant observation, structured interviews, documentation, and literature review. This study’s data analysis involved the collection, reduction, presentation, and drawing of conclusions. Data validity testing was carried out by triangulating data sources and triangulating theories. The results of the study indicate that the implementation of collateral in the Musyārakah mutanāqiṣah contract at the Bank Muamalat Indonesia Makassar branch effectively provides legal protection for the bank against the risk of default while maintaining the balance of customer rights through a transparent and fair process. The use of collateral in the Musyārakah mutanāqiṣah (MMQ) contract at Bank Muamalat Makassar is also in line with Islamic economics’ five principles, which are fairness, trustworthiness, security, prosperity, and brotherhood. This study is expected to provide new contributions in the field of Islamic economics, especially in the context of the implementation of the MMQ contract in Islamic banking at the local and national levels.